The effect of service innovation and e-service quality toward customer satisfaction the my-xl application in bandung city - Didi Tarmidi; Athifah Salsabila (Institute of Computer Science (IOCS), 2023)
This research aims to analize however the outline of Service Innovation, E-Service Quality and Customer Satisfaction, furthermore as determine how the influence of service innovation and E-Service Quality on Customer Satisfaction. The fact that businesses are required to maintain customer satisfaction serves as the background for this research, which is informed by the ever-increasingly high expectations that consumers have of a brand or product. As one of the providers, XL must also ensure customer satisfaction by enhancing or maintaining service quality.100 people who purchased active data packages and used XL cards were included in the sample. The SPSS Ver.25 data processing system is used to perform Multiple Regression Analysis as a method of data analysis. Service Innovation and E-service Quality had a significant impact on Customer Satisfaction by 42.3%, according to the analysis's estimation. The fact that the variable E-service quality is partially demonstrated to have a greater constant than the variable Service innovation must be prioritized to obtain a more significant influence.